PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TTS UNTUK MENINGKATKAN MINAT BELAJAR IPS SISWA KELAS VIII2 SMP NEGERI 4 TANAH PUTIH - Johan, Rina Selva; ', Syakroni; ', Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem this research is the students achievement of social studies SMP N 4 Tanah Putih fourth graderes still low with an average value of 67.83and minimum completenness criteria (KKM) social studiesis 75. Between students, amounting to16 people only 7 students who achieve classical KKM with 43,75%. This research is classroom action research (CAR), which aims to improve the student achievement of social studies class VIII2 at SMP N 4 Tanah Putih with implementation cooperative learning model type Think TTS. Formulation of the problem : is the implementation of cooperative learning model type TTS can improve students achievement of social studies at SMP N4 Tanah Putih. The research was conducted on February15, 2016 ‘to February29, 2016 by 2 cycles. Subjects werw students of SMP N4 Tanah Putih, totaling 16 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 69,44. In the first cycle improve an average of 69,90and an improve in the second with an average 83,20. Activities of the teacher in the learning process in cycle of 64,58% and the second meeting improve to 87,50%. In the third cycle of the first meeting and the second meeting improveKeywords : Model Of Learning Crossword Puzzles (TTS), The Results Of The Study IPS